2019
DOI: 10.21273/hortsci14366-19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Growth and Photosynthetic Parameters and Medicinal Compounds in Eleutherococcus senticosus Harms under Drought Stress

Abstract: In this investigation, changes in growth and photosynthetic parameters were used to explain the effects of drought stress on morphology and photosynthesis of Eleutherococcus senticosus. Liquid chromatography (LC)-mass spectroscopy (MS) was used to determine the content of eleutheroside B, eleutheroside E, isofraxidin, hyperoside, rutin, and kaempferol under different drought stress conditions to explain the effects of drought stress on secondary metabolism of Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The quantitative conditions of determination of eight active compounds were the same as in our previous studies (Xu et al 2019). The UPLC-MS analysis was performed with an ACQUITY UPLC system (Waters Corporation, Japan) coupled with an LC-20AD pump, SIL-20A autosampler (Waters Corporation, Japan).…”
Section: The Lc-ms Analysis Of Active Medicinal Ingredientsmentioning
confidence: 99%
“…The quantitative conditions of determination of eight active compounds were the same as in our previous studies (Xu et al 2019). The UPLC-MS analysis was performed with an ACQUITY UPLC system (Waters Corporation, Japan) coupled with an LC-20AD pump, SIL-20A autosampler (Waters Corporation, Japan).…”
Section: The Lc-ms Analysis Of Active Medicinal Ingredientsmentioning
confidence: 99%
“…Additional studies on drought stress revealed that moderate drought stress was best for the accumulation of saponins in E. senticosus and that either sufficient water or severe water deficit showed a significant reduction in saponin synthesis in E. senticosus. Additionally E. senticosus biomass and photosynthesis consistently demonstrated a significant positive correlation with the soil water content [ 20 ]. This indicates that while moderate drought stress promotes the production of E. senticosus secondary metabolites, a moist soil condition is favorable for the plant’s development and photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Its primary active components, triterpenoid saponins, are critical metrics for assessing its therapeutic quality [ 17 19 ]. Recent studies on E. senticosus show the plant thrives in moist soil environments for growth and photosynthesis, and it accumulates secondary metabolites, such as triterpenoid saponins, under moderate drought stress [ 20 ]. Studies on other medicinal plants have shown similar results, with mild drought stress favoring the synthesis and build-up of secondary metabolites in plants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth and metabolism are influenced by water deficit, which has a particularly prominent effect on photosynthesis [26]. Drought stress limits the photosynthesis and growth of plants, leading to wilting, leaf drop, and even death [27]. The root system of woad is relatively developed, and the requirements for climatic conditions and the soil environment are not strict when this species is planted.…”
Section: Introductionmentioning
confidence: 99%